Effects of glyphosate on antibiotic resistance in soil bacteria and its potential significance: A review - Bearson, Bradley L.; Douglass, Cameron H.; Duke, Stephen O.; Moorman, Thomas B.; Tranel, Patrick J. (Journal of environmental quality, 2025)
The evolution and spread of antibiotic resistance are problems with important consequences for bacterial disease treatment. Antibiotic use in animal production and the subsequent export of antibiotic resistance elements in animal manure to soil is a concern. Recent reports suggest that exposure of pathogenic bacteria to glyphosate increases antibiotic resistance. We review these reports and identify soil processes likely to affect the persistence of glyphosate, antibiotic resistance elements, and their interactions. The herbicide molecular target of glyphosate is not shared by antibiotics, indicating that target‐site cross‐resistance cannot account for increased antibiotic resistance. The mechanisms of bacterial resistance to glyphosate and antibiotics differ, and bacterial tolerance or resistance to glyphosate does not coincide with increased resistance to antibiotics. Glyphosate in the presence of antibiotics can increase the activity of efflux pumps, which confer tolerance to glyphosate, allowing for an increased frequency of mutation for antibiotic resistance. Such effects are not unique to glyphosate, as other herbicides and chemical pollutants can have the same effect, although glyphosate is used in much larger quantities on agricultural soils than most other chemicals. Most evidence indicates that glyphosate is not mutagenic in bacteria. Some studies suggest that glyphosate enhances genetic exchange of antibiotic‐resistance elements through effects on membrane permeability. Glyphosate and antibiotics are often present together in manure‐treated soil for at least part of the crop‐growing season, and initial studies indicate that glyphosate may increase abundance of antibiotic resistance genes in soil, but longer term investigations under realistic field conditions are needed. Although there are demonstratable interactions among glyphosate, bacteria, and antibiotic resistance, there is limited evidence that normal use of glyphosate poses a substantial risk for increased occurrence of antibiotic‐resistant, bacterial pathogens. Longer term field studies using environmentally relevant concentrations of glyphosate and antibiotics are needed. Plain Language Summary Recent scientific publications have indicated that the widely used herbicide glyphosate may facilitate the development of antibiotic resistance of pathogenic bacteria in agricultural soils. There are demonstratable interactions among glyphosate, bacteria, and antibiotic resistance in soil; however, the literature is conflicting, and some of the studies may not relate to conditions in agricultural soils. The authors of this review conclude that the evidence that recommended use of glyphosate poses a substantial risk for increased antibiotic‐resistant pathogens in soil needs further study. Long‐term studies using environmentally relevant concentrations of glyphosate and antibiotics are needed.